Pengaruh Audit Komunikasi Media Sosial Instagram @Kemenkominfo terhadap Kepuasan Pengguna - Wulandari, Charisma Dina; Intyaswati, Drina (Universitas Batanghari Jambi, 2024)
This research aims to find out whether communication on the social media Instagram @kemenkominfo has an effect on user satisfaction. This research used a sample of 50 @kemenkominfo Instagram users who communicated either via Instagram DM or the comments column. The indicators used in the communication variable are understanding, enjoyment, influence on attitudes, improved relationships and action. Indicators of user satisfaction variables are conformity to expectations, interest in revisiting and willingness to recommend. Using a Likert scale quantitative method and analyzed using Smart PLS 3.0. The results of this research state that communication has a positive effect on user satisfaction on Instagram @kemenkominfo, amounting to 69.5% of user satisfaction being influenced by communication variables, while the remaining 30.5% is influenced by other variables.